Community members trusted by African American parents for vaccine advice - Linda Y. Fu; Rachel Haimowitz; Danielle Thompson (Taylor & Francis Group, 2019)
Exposure to pro-vaccination messages from nonmedical peers and others perceived to share a similar value system for society (referred to as worldview outlook) improves vaccination attitudes. Nonetheless, a minority of African American parents have friends and family members who provide them with vaccine advice. The aims of the current study were to identify the presumed worldview outlook of eight types of community figures as perceived by African American parents, and determine parents' trust in these figures for vaccine advice, and whether trust varied according to the figures' racial concordance. A cross-sectional survey was administered to 110 African American parents in 2015. Parents perceived the community figures to represent a spectrum of worldview outlooks. Although levels of trust in the community figures differed overall (p < .001), it was high in the school nurse, pediatrician, mother, father, disease survivor, and vaccine scientist. All trusted figures except the father were perceived to hold a communitarian outlook. Parents shown race-concordant figures had higher levels of trust in them than those who were shown race-discordant equivalents (p < .01). These findings suggest that vaccination campaigns geared toward African American parents may be strengthened by including other nonmedical, African American spokespersons who convey their community contributions in messages.